Medical nutrition therapy in patients with severe malnutrition, unresectable gastric cancer and percutaneous endoscopic gastrostomy (PEG) - Sukawati, Cokorda Istri Mas Dalem; Harimawan, Agustinus I Wayan (Indonesian Nutrition Association, 2024)
The yearly burden of stomach cancer is expected to rise to 1.8 million new cases and 1.3 million deaths by 2040. These indicate rises of almost 63% and 66%, respectively, from 2020. This case aim to describe medical nutrition therapy in patients with unresectable gastric cancer and percutaneous endoscopic gastrostomy (PEG).